Management of patients with resistant hypertension: current treatment options - Kumar N; Calhoun DA; Dudenbostel T (Dove Medical Press, 2013)
Nilay Kumar,1 David A Calhoun,2 Tanja Dudenbostel21Department of Medicine, 2Division of Cardiovascular Disease, Hypertension and Vascular Biology Program, University of Alabama at Birmingham, Birmingham, AL, USAAbstract: Resistant hypertension (RHTN) is an increasingly common clinical problem that is often heterogeneous in etiology, risk factors, and comorbidities. It is defined as uncontrolled blood pressure on optimal doses of three antihypertensive agents, ideally one being a diuretic. The definition also includes controlled hypertension with use of four or more antihypertensive agents. Recent observational studies have advanced the characterization of patients with RHTN. Patients with RHTN have higher rates of cardiovascular events and mortality compared with patients with more easily controlled hypertension. Secondary causes of hypertension, including obstructive sleep apnea, primary aldosteronism, renovascular disease, are common in patients with RHTN and often coexist in the same patient. In addition, RHTN is often complicated by metabolic abnormalities. Patients with RHTN require a thorough evaluation to confirm the diagnosis and optimize treatment, which typically includes a combination of lifestyle adjustments, and pharmacologic and interventional treatment. Combination therapy including a diuretic, a long-acting calcium channel blocker, an angiotensin-converting enzyme inhibitor, a beta blocker, and a mineralocorticoid receptor antagonist where warranted is the classic regimen for patients with treatment-resistant hypertension. Mineralocorticoid receptor antagonists like spironolactone or eplerenone have been shown to be efficacious in patients with RHTN, heart failure, chronic kidney disease, and primary aldosteronism. Novel interventional therapies, including baroreflex activation and renal denervation, have shown that both of these methods may be used to lower blood pressure safely, thereby providing exciting and promising new options to treat RHTN.Keywords: RHTN, blood pressure, chlorthalidone, hydrochlorothiazide, baroreflex activation, renal denervation, aldosterone, heart failure, renovascular, obstructive sleep apnea